2021
DOI: 10.3390/math9141677
|View full text |Cite
|
Sign up to set email alerts
|

Cryptocurrency Portfolio Selection—A Multicriteria Approach

Abstract: This paper proposes the PROMETHEE II based multicriteria approach for cryptocurrency portfolio selection. Such an approach allows considering a number of variables important for cryptocurrencies rather than limiting them to the commonly employed return and risk. The proposed multiobjective decision making model gives the best cryptocurrency portfolio considering the daily return, standard deviation, value-at-risk, conditional value-at-risk, volume, market capitalization and attractiveness of nine cryptocurrenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 50 publications
(66 reference statements)
0
10
0
Order By: Relevance
“…In addition, many innovative methods are proposed for reference in terms of how to analyze the data of virtual cryptocurrency transactions and how to select variables. In literature [25], for example, this paper proposes a virtual encryption based on PROMETHEE II currency trading portfolio selection criterion method, and the model of sample performance with five other kinds commonly used the optimal portfolio model; according to the index of all observed, the proposed model is better than all the other models, where the odds ratio is from 50 to 94%. The literature also suggests the benefits of adopting more currency standards and an appropriate multi-parameter approach in the analysis and selection process of virtual cryptocurrency transaction data.…”
Section: Research Status Of Virtual Cryptocurrencymentioning
confidence: 99%
“…In addition, many innovative methods are proposed for reference in terms of how to analyze the data of virtual cryptocurrency transactions and how to select variables. In literature [25], for example, this paper proposes a virtual encryption based on PROMETHEE II currency trading portfolio selection criterion method, and the model of sample performance with five other kinds commonly used the optimal portfolio model; according to the index of all observed, the proposed model is better than all the other models, where the odds ratio is from 50 to 94%. The literature also suggests the benefits of adopting more currency standards and an appropriate multi-parameter approach in the analysis and selection process of virtual cryptocurrency transaction data.…”
Section: Research Status Of Virtual Cryptocurrencymentioning
confidence: 99%
“…PROMETHEE II is also applied in cryptocurrency studies. Researchers such as Kądziołka [33] and Aljinović et al [34] employed the PROMETHEE II methodology in the field of cryptocurrencies. Kądziołka [33] used the PROMETHEE II method to create a ranking of cryptocurrency exchanges.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we go further than ranking projects and provide a framework for rating them. Aljinović et al [34] use PROMETHEE II for cryptocurrency portfolio selection and cite "incorporating criteria that, to the best of our knowledge, have never been used before in portfolio optimization" as one of their contributions to the existing literature. We also develop special criteria that, to the best of our knowledge, have never been used before in blockchain project evaluations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Paper [10] deals with cryptocurrency portfolio selection and applies a multi-criteria approach based on PROMETHEE II. The authors found that their model gave the best cryptocurrency portfolio when considering the daily return, the standard deviation, the value-at-risk, the conditional value-at-risk, the volume, the market capitalization as well as nine cryptocurrencies for the period from January 2017 to February 2020.…”
mentioning
confidence: 99%